Information quality of videos related to adolescent depression on social media platforms: a comparative study of TikTok and BiliBili - Wang, Guiyun; Kuang, Jinke; Qi, Yanxia; Li, Jingya (Frontiers in Public Health, 2025)
BackgroundThe incidence of adolescent depression has been increasing globally in recent years, raising concern among the public about this condition. Videos on adolescent depression are disseminated through TikTok and Bilibili, both of which have gained popularity in recent years as easily accessible sources of health information. However, no researchers have conducted professional inspection and evaluation of depression-related videos targeting adolescents, some of these videos may even disseminate misleading information.MethodsWe retrieved the top 100 adolescent depression related videos from TikTok and Bilibili. Data on video characteristics, including engagement metrics and content, were also collected. Video quality was assessed using three rating tools: the Journal of the American Medical Association (JAMA), Global Quality Score (GQS), and the Modified DISCERN (mDISCERN). The independent t-test, Mann–Whitney U test, and Kruskal–Wallis test were used for comparison and analysis.ResultsThe analysis included 188 videos, with 95 from TikTok and 93 from Bilibili. TikTok videos were shorter and exhibited higher audience interaction. The most popular topic on TikTok and Bilibili was “Symptoms of adolescent depression.” Video creators were predominantly experts on TikTok (72.63%), and general users on Bilibili (56.99%). Video quality, assessed using JAMA, GQS, and mDISCERN, varied across platforms. There were statistically significant differences in the three quality scores among different types of creators on TikTok and Bilibili (P < 0.005). No significant differences were observed in views, likes, comments, and collections data across different video publishers on TikTok and Bilibili.ConclusionVideos on social media platforms can help the public gain knowledge about adolescent depression. However, the quality of video from all platforms requires improvement. Strengthening collaboration among content creators, mental health experts, and platform administrators may enhance video quality and ensure more accurate and effective dissemination of information.